The S Genome Segment Is Sufficient to Maintain Pathogenicity in Intra-Clade Lassa Virus Reassortants in a Guinea Pig Model - Welch, Stephen R.; Scholte, Florine E. M.; Albariño, César G.; Kainulainen, Markus H.; Coleman-McCray, JoAnn D.; Guerrero, Lisa Wiggleton; Chakrabarti, Ayan K.; Klena, John D.; Nichol, Stuart T.; Spengler, Jessica R.; Spiropoulou, Christina F. (Frontiers in Cellular and Infection Microbiology, 2018)
Genome reassortment in Lassa virus (LASV) has been reported in nature, but phenotypic consequences of this phenomenon are not well described. Here we characterize, both in vitro and in vivo, reassortment between 2 LASV strains: the prototypic 1976 Josiah strain and a more recently isolated 2015 Liberian strain. In vitro analysis showed that although cis- and trans-acting elements of viral RNA synthesis were compatible between strains, reassortants demonstrated different levels of viral replication. These differences were also apparent in vivo, as reassortants varied in pathogenicity in the guinea pig model of LASV infection. The reassortant variant containing the Josiah S segment retained the virulence of the parental Josiah strain, but the reassortant variant containing the S segment of the Liberian isolate was highly attenuated compared to both parental strains. Contrary to observations in reassortants between LASV and other arenavirus species, which suggest that L segment-encoded factors are responsible for virulence, these studies highlight a role for S segment-encoded virulence factors in disease, and also suggest that inefficient interactions between proteins of heterologous strains may limit the prevalence of reassortant LASV variants in nature.